Facilitating Climate Smartness in Extension Service Delivery and Impacting Farmers in Ghana - Yeboah, Stephen; Adomako, Joseph; Amankwaa-Yeboah, Patricia; Haleegoah, Joyce; Frimpong-Anin, Kofi; Amengor, Natson Eyram; Dalaa, Mustapha Alasan; Damba, Osman T; Kyere, Reginald; Obeng, Faustina; Tepa-Yotto, Ghislain (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The project intervention communities of The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) in Ghana are vulnerable to climate variability and change, which continues to pose a threat to food crop production. Increasing the resilience of the communities includes building their capacity on climate smart agriculture practices (CSA), climate information services (CIS) and One-health (OH) innovations. A Training of Trainers workshop was organized and Thirty-six Master trainers (mainly extension officers) received training on CSA, CIS, and OH innovations. The TOT followed a series of trainings on CSA, CIS, and OH innovations in 2022. The Master trainers were mandated to roll out the training in all AICCRA intervention regions to farmers. A total of four thousand and ninety-three (4093) farmers were trained directly with 53% being female and about 40,930 farmers likely benefitted indirectly from the training offered to the farmers by the master trainers. A follow-up study was commissioned to track outcome impact case stories/success stories of the AICCCRA trainings. The study employed focused group discussions to gain an in-depth understanding of the impact of the training on extension officers and farmers. Results showed significant improvements in the trainees' technical knowledge related to the interpretation and application of weather forecasts, smart seed varieties, fertilizer application, chemical application, and farm management as well as climate-smart farming. In terms of engagement between Agricultural Extension Agents (AEAs) and farmers, the training has improved the confidence of the AEAs in extension delivery using a Face-to-Face approach in teaching climate-smart farming, OH technologies, and interpreting CIS. The results showed a positive shift in farmers' reception to improved climate-smart technologies, with increased interest and requests for information. In terms of changes in farm management, yield, and income of farmers, there were improvements in farm management by farmers, including the use of certified seeds, fertilizers, and chemical application, and improved yield and profit margin of farmers with a positive impact on income. Widely, extension officers expressed high satisfaction with the training approaches, considering them timely, appropriate, and beneficial in delivering climate smartness in Ghana’s agriculture. The major constraints faced by extension officers across locations in the transfer of knowledge to farmers include lengthy training duration, difficulty in accessing smart technologies including smart seeds, inadequate motorbikes for commutation, and logistical constraints including inadequate training materials. Capacity strengthening of Extension officers and farmers has proven to have a high potential to improve agricultural risk management in Ghana.